HEURISTIK SISWA PEREMPUAN SMP DALAM MEMECAHKAN MASALAH POLA BILANGAN - Iva Desi Ruliani; Yusuf Fuad; Rooselyna Ekawati (IKIP Siliwangi, 2022)
This study aims to describe the heuristics of female junior high school students in solving number pattern problems. Two subjects were selected through the provision of a mathematical ability test (TKM) and a problem-solving test (TPM 1) in class VIII E of SMP AL-Hikmah 2 Benda. The instrument used for problem solving test (TPM 1 & 2), and interview guide. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The results showed that female students used heuristics to make systematic lists, guess & check, and use models in solving number pattern problems. In addition, female students use their visual representation skills by making guide lines that are used to find the nth pattern and help use their intuition by counting manually until a developed pattern is found. Female students also use the ability to generalize to get the formula for the nth pattern and use knowledge about the types of number patterns to be able to guess the formula for the nth pattern.